2020
DOI: 10.3390/f11121325
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of Speciation in the Central Sandy Steppe, Woody Steppe Area of the Carpathian Basin through the Example of Festuca Taxa

Abstract: Research Highlights: We examined the vegetation appearing in forest-steppes in the Pannon region. In the present survey taxonomical relations of the dominant Festuca species were examined. Background and Objectives: After deforestation and shrubcutting bare soil patches exposed to anthropogenous effects provided an opportunity for new vegetation to form. Materials and Methods: Inflorescence parameters and micromorphological characters of the leaves were examined in a new taxon and compared with two, presumably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
1
6
0
1
Order By: Relevance
“…These trends are similar to those of other publications (Kiss et al, 2008(Kiss et al, , 2011. The vegetation of young fallow is often rich in degradation and weed species in other studies (Albert et al, 2014;Csecserits et al, 2011;Kelemen et al, 2010;Török et al, 2011;Valkó et al, 2010;Fülöp et al, 2020Fülöp et al, , 2021Bódis et al, 2021;Penksza et al, 2008Penksza et al, , 2010Penksza et al, , 2020Penksza et al, , 2021. Based on the relative ecological values of the species, the slopes of Kaposdada are the closest to the natural ones, among them the pastures formed in the lower third of the pasture.…”
supporting
confidence: 88%
“…These trends are similar to those of other publications (Kiss et al, 2008(Kiss et al, , 2011. The vegetation of young fallow is often rich in degradation and weed species in other studies (Albert et al, 2014;Csecserits et al, 2011;Kelemen et al, 2010;Török et al, 2011;Valkó et al, 2010;Fülöp et al, 2020Fülöp et al, , 2021Bódis et al, 2021;Penksza et al, 2008Penksza et al, , 2010Penksza et al, , 2020Penksza et al, , 2021. Based on the relative ecological values of the species, the slopes of Kaposdada are the closest to the natural ones, among them the pastures formed in the lower third of the pasture.…”
supporting
confidence: 88%
“…Festuca rupicola is a dominant grassland species on the loess grasslands (Salvio nemorosae-Festucetum rupicolae) and it is the namesake species of the association. However, there is also a diversity of Festuca taxa on areas of verges and patches of loess grasslands in the landscape (Tompapuszta, Bökény Cumanian mound) [55,56]. Festuca specimens with narrower leaves than F. rupicola and with more significant differences in size (Penksza 2009) in inflorescence parameters were also found, which could belong to several species.…”
Section: Discussionmentioning
confidence: 99%
“…During this study, taxa with a transitional sclerenchyma form were also found in the area, which could be observed in species with a bundle sclerenchyma [54,55]. The Festuca javorkae, which was related to Festuca rupicola, could also be problematic, although this species was clarified [55][56][57] and its species differentiation was shown using molecular studies by Galli et al [58][59][60]. After clarifying the taxa, our aims were to investigate the multivariate statistical assessment of loess grasslands occurring in different habitats and to reveal the patterns of occurrence of grasslands in the area of the Cumanian mounds.…”
Section: Introductionmentioning
confidence: 99%
“…A gyep leromlása komplex dinamikus folyamatokat foglal magába: elsivatagosodás, talajtömörödés, fakitermelés, erózió (Kovdaa, 1976;Li et al, 2006) vagy a becserjésedés (Pápay, 2016;Pápay és Uj, 2012;Pápay et al, 2017Pápay et al, , 2019bPápay et al, , 2020Penksza et al, 2015. Liu (2006) megállapítása szerint a gyep leromlásának további tipikus jellemzői a növényi lefedettség csökkenése, homokosodás, illetve a sósodás (Török et al, 2014;Penksza et al, 2020). Továbbá csökken a növényzet a különböző felhasználási célokra (takarmánytermelés), megnövekszik a mérgező fajok aránya, valamint csökken a gyökérzóna vízmegtartó képessége (Zhang és Liu, 2003;Cui és Graf, 2009;Ma et al, 2018).…”
unclassified